Polsko-serbskie kontakty literackie – nowe spojrzenie - Kręzel, Piotr (Zeszyty Cyrylo-Metodiańskie, 2022)
Polish-Serbian Overview of Literary Relations – a Fresh Look: A review of: Ajdačić, Dejan. Polish-Serbian Literary Relations. Translations and Reception (In Serbian: Poljsko-srpske književne veze. Prevodi i recepcija). University of Gdansk Press, 2021, 124 pp. ISBN 978-83-8206-249-6.